On the existence of cellular tocopheryl phosphate, its synthesis, degradation and cellular roles: A hypothesis - (:unkn) unknown (WILEY, 2005)
The finding that alpha-tocopheryl phosphate is present in cells in small amounts, that it can be synthesized and hydrolyzed supports the hypothesis that alpha-tocopheryl phosphate might be a signaling molecule. The possible pathways needed for the synthesis, hydrolysis and signaling are considered in this hypothesis as well the possible extension of this reaction to additional molecules such as tocopherols and tocotrienols. A possible mechanism of action of other tocopherol esters ( succinate and maleate) is also hypothesized.
Keywords: alpha-tocopherol; vitamin E; tocopherol esters; alpha-tocopheryl phosphate; cell signaling; VITAMIN-E; GAMMA-TOCOPHEROL; ANTIOXIDANT; EXPRESSION; PROLIFERATION; CLONING